The philosopher's plant : an intellectual herbarium - Marder, Michael, 1980- (European perspectives. A series in social thought and cultural criticism., 2014)
Despite their conceptual allergy to vegetal life, philosophers have used germination, growth, blossoming, fruition, reproduction, and decay as illustrations of abstract concepts; mentioned plants in passing as the natural backdrops for dialogues, letters, and other compositions; spun elaborate allegories out of flowers, trees, and even grass; and recommended appropriate medicinal, dietary, and aesthetic approaches to select species of plants. In this book, Michael Marder illuminates the elaborate vegetal centerpieces and hidden kernels that have powered theoretical discourse for centuries.